2019
DOI: 10.3892/mmr.2019.10145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrin β1 in the treatment of stress urinary incontinence by electrical stimulation

Abstract: The aim of the present study was to investigate the protective effect of integrin β1 in the treatment of stress urinary incontinence (SUI) by electrical stimulation, and the underlying mechanisms by which electrical stimulation regulates the collagen metabolism of female vaginal wall fibroblasts (FVWFs). FVWFs obtained from the vaginal wall tissue of patients with (Ingelman-Sundberg scale; grade II, n=8; grade III, n=10) or without (n=8) SUI during gynecological operations were isolated by enzymatic digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…All studies included women and female animals only. Of the human studies, SUI alone was investigated in 52 human studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], and SUI with the co-occurrence of POP in 23 studies [ 62 , 72 , 73 , 74 ...…”
Section: Resultsmentioning
confidence: 99%
“…All studies included women and female animals only. Of the human studies, SUI alone was investigated in 52 human studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], and SUI with the co-occurrence of POP in 23 studies [ 62 , 72 , 73 , 74 ...…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is not clear which cell sensor received ES to promote TGF-β1 and α-SMA expression. TGF-β1-mediated signals are enhanced via integrin β1, which is a cell surface receptor 24 )…”
Section: Discussionmentioning
confidence: 99%
“…It is a complex long-chain protein mixture, composed of collagen, elastin, and proteoglycan 18 . Previous studies have con rmed that ECM remodeling is an important association in the pathogenesis of SUI 19 . It has been found that estrogen affects the transcription and expression of collagen, which are the main component of ECM 20 .…”
Section: Introductionmentioning
confidence: 95%
“…Meanwhile, reports on the remodeling of ECM caused by estrogen are not systematic. Therefore, in this article, according to our previous experience 25 , we constructed the animal model of stress urinary incontinence by vaginal dilation, and correspondingly, we constructed the mechanical injury model of L929 broblasts 26 . We have described the application of topical estrogen to treat SUI from the animal and cellular level to investigate the reasons affecting the e cacy of topical estrogen for SUI, the mechanism by which estrogen affects the expression of ECM, and then pave the way for the mechanism of treatment effects.…”
Section: Introductionmentioning
confidence: 99%